Gender Dynamics in the Planning Workplace: The Importance of Women in Management. Issue 2 (2nd April 2020) - Turesky, Marisa; Warner, Mildred E.
Abstract: Problem, research strategy, and findings: Planners' workplaces are diversifying with respect to gender, but office culture and policies do not always reflect such change. Our research explores the influence of gender, management, and organizational characteristics on planners' perceptions of workplace culture and benefits. We conducted a national survey with the APA's Women and Planning Division in 2015 to assess whether planners' perceptions regarding workplace culture and benefits differ by gender and organizational characteristics of the planning office. A limitation of the survey is the small self-selected sample of mostly female respondents. We combine feminist planning theory with workplace psychology theories of expectation states, role congruity, and representative bureaucracy, as well as transformational leadership, to explain workplace dynamics in planning agencies. Qualitative analysis shows problems with exclusive communication and equal opportunity are linked to management characteristics. To test this, we build five regression models on gender respect, exclusive communication, work–life benefits, flexibility perception, and equal opportunity. Our regression models control for gender, age, experience of respondent, and organizational characteristics. Our results indicate that gender respect, work–life benefits, and flexibility perception do not differ by gender. However, women are less likely to feel heard in their workplace (exclusive communication) or perceive equal opportunity. Workplaces with female management are more likely to show sensitivity to gender issues, support for flexible benefits, and equal opportunity for pay and advancement. Takeaway for practice: These results suggest planners feel they can raise gender issues and access flexibility benefits without prejudice. But planning workplaces need to address problems with exclusive communication and women's perceptions of unequal opportunities for pay and advancement. Introducing gender-inclusive planning and leadership development curriculum to planning programs would prepare future planners; and ongoing training for management may improve behavior, communication, and benefits for all genders in planning workplaces.